2017
DOI: 10.1159/000455936
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Perturbs Bone Microarchitecture and Bone Strength through Regulation of Sema3A/IGF-1/β-Catenin in Rats

Abstract: Purpose: Increasing evidence supported that semaphorin 3A (Sema3A), insulin-like growth factor (IGF)-1 and β-catenin were involved in the development of osteoporosis and diabetes. This study is aimed to evaluate whether Sema3A/IGF-1/β-catenin is directly involved in the alterations of bone microarchitecture and bone strength of diabetic rats. Methods: Diabetic rats were induced by streptozotocin and high fat diet exposure. Bone microarchitecture and strength in the femurs were evaluated by micro-CT scanning, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 51 publications
(52 reference statements)
8
39
0
Order By: Relevance
“…In addition, DKK1 prevents Wnt binding to the extracellular regions and accordingly inhibits Wnt signal transduction and its subsequent bone‐forming effect (Zhou et al, ). Our results also confirmed that ovariectomy inhibited Wnt/β‐catenin signaling via increasing the expression of DKK1 and decreasing LRP6 expression as well as regulating the relative ratios of p‐GSK3β to GSK3β and p‐β‐catenin to β‐catenin, which further leads to β‐catenin degradation and subsequent bone loss (Ma et al, ). Administration of RSM to OVX rats for 14 weeks significantly antagonized DKK1 expression and increased p‐LRP6 expression and the relative ratio of p‐GSK3β to GSK3β, as well as decreased the relative expression of p‐β‐catenin to β‐catenin in the rat tibias, resulting in osteoblasts differentiation and maturation as well as bone improvement.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In addition, DKK1 prevents Wnt binding to the extracellular regions and accordingly inhibits Wnt signal transduction and its subsequent bone‐forming effect (Zhou et al, ). Our results also confirmed that ovariectomy inhibited Wnt/β‐catenin signaling via increasing the expression of DKK1 and decreasing LRP6 expression as well as regulating the relative ratios of p‐GSK3β to GSK3β and p‐β‐catenin to β‐catenin, which further leads to β‐catenin degradation and subsequent bone loss (Ma et al, ). Administration of RSM to OVX rats for 14 weeks significantly antagonized DKK1 expression and increased p‐LRP6 expression and the relative ratio of p‐GSK3β to GSK3β, as well as decreased the relative expression of p‐β‐catenin to β‐catenin in the rat tibias, resulting in osteoblasts differentiation and maturation as well as bone improvement.…”
Section: Discussionsupporting
confidence: 84%
“…The fixed uteri and decalcified femurs were defatted and dehydrated with xylene and graded ethanol (50–100%) and embedded in paraffin. Then 5‐μm paraffin sections were prepared by automated microtome (Leica; Wetzlar, Germany) and used for the stainings of H&E and Safranin O/Fast green according to the protocols as previously described (Guo et al, ; Ma et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This protective effect is thought to be modulated via naringin-induced increase in Semaphorin 3A expression in vivo, a local factor of the bone microenvironment that simultaneously promotes bone formation while reducing bone resorption [49]. However, Semaphorin 3A deficiency is directly implicated in the disruption of bone remodeling and subsequent bone loss in diabetic rats [50]. This might explain why naringin successfully prevented bone loss in a rat model of streptozotocin-induced diabetes [51].…”
Section: Preclinical In Vivo Studiesmentioning
confidence: 99%
“…Insulin-like growth factor-1 (IGF-1) is a peptide with a molecular mass of 7.6 kDa that is produced in the liver and secreted into the circulation [7][8]. It regulates cell survival, proliferation, differentiation, and metabolism [7], and is especially important in the circulatory system [9].…”
Section: Introductionmentioning
confidence: 99%